Pralsetinib for RET fusion-positive non-small-cell lung cancer (ARROW): a multi-cohort, open-label, phase 1/2 study. Issue 7 (July 2021) - Gainor, Justin F; Curigliano, Giuseppe; Kim, Dong-Wan; Lee, Dae Ho; Besse, Benjamin; Baik, Christina S; Doebele, Robert C; Cassier, Philippe A; Lopes, Gilberto; Tan, Daniel S W; Garralda, Elena; Paz-Ares, Luis G; et al.
Summary: Background: Oncogenic alterations in RET have been identified in multiple tumour types, including 1–2% of non-small-cell lung cancers (NSCLCs). We aimed to assess the safety, tolerability, and antitumour activity of pralsetinib, a highly potent, oral, selective RET inhibitor, in patients with RET fusion-positive NSCLC. Methods: ARROW is a multi-cohort, open-label, phase 1/2 study done at 71 sites (community and academic cancer centres) in 13 countries (Belgium, China, France, Germany, Hong Kong, Italy, Netherlands, Singapore, South Korea, Spain, Taiwan, the UK, and the USA). Patients aged 18 years or older with locally advanced or metastatic solid tumours, including RET fusion-positive NSCLC, and an Eastern Cooperative Oncology Group performance status of 0–2 (later limited to 0–1 in a protocol amendment) were enrolled. In phase 2, patients received 400 mg once-daily oral pralsetinib, and could continue treatment until disease progression, intolerance, withdrawal of consent, or investigator decision. Phase 2 primary endpoints were overall response rate (according to Response Evaluation Criteria in Solid Tumours version 1·1 and assessed by blinded independent central review) and safety. Tumour response was assessed in patients with RET fusion-positive NSCLC and centrally adjudicated baseline measurable disease who had received platinum-based chemotherapy or were treatment-naive because they were ineligible for standard therapy. This ongoing study is registered with ClinicalTrials.gov, NCT03037385, and enrolment of patients with treatment-naive RET fusion-positive NSCLC was ongoing at the time of this interim analysis. Findings: Of 233 patients with RET fusion-positive NSCLC enrolled between March 17, 2017, and May 22, 2020 (data cutoff), 92 with previous platinum-based chemotherapy and 29 who were treatment-naive received pralsetinib before July 11, 2019 (efficacy enrolment cutoff); 87 previously treated patients and 27 treatment-naive patients had centrally adjudicated baseline measurable disease. Overall responses were recorded in 53 (61%; 95% CI 50–71) of 87 patients with previous platinum-based chemotherapy, including five (6%) patients with a complete response; and 19 (70%; 50–86) of 27 treatment-naive patients, including three (11%) with a complete response. In 233 patients with RET fusion-positive NSCLC, common grade 3 or worse treatment-related adverse events were neutropenia (43 patients [18%]), hypertension (26 [11%]), and anaemia (24 [10%]); there were no treatment-related deaths in this population. Interpretation: Pralsetinib is a new, well-tolerated, promising, once-daily oral treatment option for patients with RET fusion-positive NSCLC. Funding: Blueprint Medicines.